2021
DOI: 10.1111/bph.15523
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cocaine exposure in adolescence: Behavioural effects and neuroplastic mechanisms in experimental models

Abstract: Drug addiction is a devastating disorder with a huge economic and social burden for modern society. While an individual may slip into drug abuse throughout his/her life, adolescents are at higher risk but, up to date, only few studies attempted to elucidate the underlying cellular and molecular bases of such vulnerability. Indeed, preclinical evidence indicates that psychostimulants and adolescence interact and contribute to promoting a dysfunctional brain.In this review, we have focused our attention primaril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 146 publications
1
9
0
Order By: Relevance
“…Consistent with our previous finding (18), we found that ACE mice exhibited obvious anxiety-like behaviors in their adulthood, which was efficiently suppressed by electro-acupuncture (EA) at acupoints of Baihui (GV 20 Drug abuse such as cocaine during adolescence, a sensitive period of heightened propensity to substance use in humans, enhance risk of developing psychiatric disorders, which even persist into adulthood (2,10,28). Consistent with human and animal studies on ACE (9,18,29,30), ACE mice exhibited more anxiety in their adulthood here.…”
Section: Discussionsupporting
confidence: 86%
“…Consistent with our previous finding (18), we found that ACE mice exhibited obvious anxiety-like behaviors in their adulthood, which was efficiently suppressed by electro-acupuncture (EA) at acupoints of Baihui (GV 20 Drug abuse such as cocaine during adolescence, a sensitive period of heightened propensity to substance use in humans, enhance risk of developing psychiatric disorders, which even persist into adulthood (2,10,28). Consistent with human and animal studies on ACE (9,18,29,30), ACE mice exhibited more anxiety in their adulthood here.…”
Section: Discussionsupporting
confidence: 86%
“…In general, proper stratification before initiation of clinical trials for substance use disorders is currently insufficient. Gender differences in responding to psychostimulants or psychostimulant-associated cues is well-known, and the same counts for differences between adolescents vs. adults ( Kosten et al, 1996 ; Lynch et al, 2008 ; Wong et al, 2013 ; Runegaard et al, 2017 ; Caffino et al, 2021 ), yet many clinical trials base their analysis on mixed genders and wide age groups (see Tables 1 , 2 ). The sex differences in treatment efficacy seen for both disulfiram, atomoxetine and bupropion highlight this need for stratification, since some of the negative treatment outcomes of clinical trials might stem from the combination of low patient numbers combined with mixed genders and random age groups being combined ( Nich et al, 2004 ; Pani et al, 2010 ; Heinzerling et al, 2013 ; Heinzerling et al, 2014 ; DeVito et al, 2017b ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, alterations in dopaminergic neurotransmission play a fundamental role in the increased susceptibility to drug addiction onset, and the developing brain is particularly sensitive to the detrimental effects of drug-induced neurotransmission dysregulation. As a consequence, alterations in the neurocircuitry resulting from drug use in adolescence can increase the susceptibility to drug use at a later age ( Caffino et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%